Microplastic composition in water, sediment, and fish in the Middle Section of the Kahayan River: Implications for the sustainability of floating net cage aquaculture - Muhammad Aldair Mukstofa Carda; Zakiah; Syahnan Aly Lubis (Acta Aquatica: Aquatic Sciences Journal, 2026)
Microplastics are emerging pollutants widely detected in freshwater ecosystems, including rivers that act as major pathways for plastic waste transport to the ocean. This study aimed to analyze the abundance and characteristics of microplastics in water, sediment, and fish from the middle section of the Kahayan River and to assess their implications for the sustainability of floating net cage aquaculture. Sampling was conducted at five stations representing different levels of anthropogenic activity. Water, sediment, and fish samples were processed using the wet peroxide oxidation (WPO) and NaCl density separation methods, followed by microscopic identification. The results revealed that microplastics were widely distributed across all environmental compartments, with mean abundances of 3,14 particles/L in water, 7,31 particles/kg-dw in sediment, and 3,63 particles/individual in fish. The highest concentrations were found in stations with intensive aquaculture, dense settlements, and active trading areas. The dominant types were fibers and fragments, mainly white, blue, and black/gray in color. Particles <300 µm predominated in water and fish, whereas those >1000 µm were more abundant in sediment. These findings indicate the transfer of microplastics from abiotic to biotic components, suggesting potential bioaccumulation within the aquatic food chain. The presence of microplastics in aquaculture environments may degrade water and fish quality, posing threats to aquaculture sustainability and food safety for local communities along the Kahayan River. Keywords: Fish; Floating net cage; Kahayan River; Microplastics